Variation in the advanced fiber information system cotton fiber length-by-number distribution captured by high volume instrument fiber length parameters. Issue 7 (April 2018) - Kelly, Brendan R; Hequet, Eric F
Variation in cotton fiber length impacts processability at the mill and the quality of spun yarns. The High Volume Instrument (HVI) and Advanced Fiber Information System (AFIS) are cotton fiber quality assessment instruments able to quickly assess a myriad of fiber quality characteristics. HVI testing provides the fiber length parameters most widely utilized by the cotton industry, Upper Half Mean Length and Uniformity Index. However, HVI fiber length parameters do not account for the complete within-sample variation in fiber length, such as the shortest fibers in the sample. AFIS testing is able to characterize the complete within-sample distribution of fiber length within a sample of cotton by evaluating individual fibers. Within-sample variation in fiber length is an important cotton fiber quality concern because it impacts processing performance and yarn quality. In this paper, the fiber length for 9127 commercial cotton bales was evaluated on both HVI and AFIS. The AFIS length distributions are used to characterize the complete distribution of fiber length within each bale. A novel statistical technique is introduced and is used to characterize a set of multivariate axes that characterize the total within-bale variation in fiber length among the complete set of commercial bales. These results suggest that less than half of the variation in cotton fiber length captured by the AFIS length distributions is captured by the two length parameters provided by HVI testing. If an experimental factor has no significant impact on an HVI fiber quality parameter, an alternative cotton fiber length measurement such as the AFIS length distribution should be considered.